Emerging antiangiogenic therapies for non-small-cell lung cancer. Issue 10 (October 2011) - Blakely, Collin; Jahan, Thierry
Lung cancer remains the leading cause of cancer-related deaths. Antiangiogenic therapy has increasingly been studied for advanced non-small-cell lung cancer (NSCLC). Bevacizumab is the only approved antiangiogenic agent for NSCLC and has shown progression-free survival benefits in large Phase III studies and an overall survival benefit in the Phase III E4599 trial in advanced nonsquamous NSCLC. New antiangiogenic treatment strategies are being evaluated that target multiple receptors within a family (VEGF receptor [VEGFR]-1, VEGFR-2) or multiple angiogenic pathways (targets VEGFR and PDGF receptor pathways), and agents that inhibit alternative mediators of angiogenesis (integrins and established vasculature). As data become available from ongoing studies, it will be important to determine how these new antiangiogenic agents will best fit into the current NSCLC treatment paradigm.